Cutaneous Adverse Events of Immune Checkpoint Inhibitors: A Literature Review - Zoe Apalla; Chryssoula Papageorgiou; Aimilios Lallas; Florentina Delli; Christina Fotiadou; Christina Kemanetzi; Elizabeth Lazaridou (Mattioli1885, 2021)
Immune checkpoints assist with self-tolerance and minimize collateral tissue damage when immune responses are activated. Although immune checkpoint inhibitors (CPIs) are characterized by a favorable risk/benefit ratio, immune checkpoint blockade has been associated with a new subset of autoimmune-like toxicities, named immune-related adverse events (irAEs). Dermatologic reactions are among the most prevalent irAE triggered by CPIs. In a majority of cases they are self-limiting and readily manageable. However, it is not uncommon that they result in severe skin involvement and impairment of patients' quality of life. Awareness of the spectrum of cutaneous irAEs is mandatory for every clinician involved in the management of oncologic patients. The role of the dermatologists is essential because early recognition and appropriate management of skin toxicity may prevent dose modifications and discontinuation of CPIs. The latter is particularly relevant, considering that recent data suggest favorable oncologic response in patients developing irAEs.